Strategi Pemasaran Holistik Bank Syariah dalam Meningkatkan Kualitas Layanan E-Banking - Muhammad Awalul Akhyar; Aji Damanuri (Institut Agama Islam Negeri Ponorogo, 2022)
The development of technology has radically changed the banking transaction system, which altered the banking culture. The public has responded positively to e-banking services as a safe, reliable, and efficient payment system solution. Banking institutions such as Islamic banks need to have a holistic and standardized marketing strategy to be implemented in e-banking service products so that Islamic banks can survive in the current era of technological development. This research relates to the holistic marketing strategy of Islamic banks in improving the quality of e-banking services. This study aims to describe and analyze the strategy, tactics, and values ​​that Bank Syariah Mandiri Ponorogo Branch Office uses to improve the quality of e-banking services to realize quality e-banking marketing and services.